Ethnic differences in early glycemic control in childhood-onset type 1 diabetes. Issue 1 (7th August 2017) - Khanolkar, Amal R; Amin, Rakesh; Taylor-Robinson, David; Viner, Russell M; Warner, Justin; Gevers, Evelien F; Stephenson, Terence
Abstract : Some ethnic minorities with type 1 diabetes (T1D) have worse glycemic control (higher glycated hemoglobin (HbA1c )) and increased risk for vascular complications. There is limited evidence on the impact of ethnicity on early glycemic control when most patients experience transient remission postdiagnosis. We examined associations between ethnicity and longitudinal HbA1c trajectories during the first 6 months postdiagnosis in a multiethnic cohort in East London. Research design and methods: Data on 443 (50% female) children <19 years of age, with T1D and attending one of three clinics in East London between January 2005 and December 2015 were included. Linear mixed-effects modeling was used to assess ethnic differences in longitudinal HbA1c trajectories during the first 6 months postdiagnosis (1, 028 HbA1c data points), adjusting for sex, age at diagnosis, socioeconomic status and pH at diagnosis. Growth curve modeling was used to plot discrete HbA1c trajectories by ethnicity. Results: Longitudinal modeling revealed that all ethnic minorities had higher mean HbA1c at diagnosis compared with White children and highest in Bangladeshi (9.7 mmol/mol, 95% CI 5.1 to 14.3), Asian-Other (5.8 mmol/mol, 95% CI 2.2 to 9.3) and Somali (5.2 mmol/mol, 95% CI 0.1 to 10.2) children, and these differences persisted over the 6-month period after diagnosis. During the first month, HbA1c decreased on average by 19.6 mmol/mol (95% CI −21 to −18) for all children. Population averaged HbA1c decreased between diagnosis and 4 months, followed by a gradual increase in HbA1c levels (mean difference of −30 mmol/mol between diagnosis and 6 months). Conclusions: Ethnic minorities present with higher HbA1c at diagnosis, with the largest mean differences observed in Bangladeshi, Asian-Other and Somali children. These higher levels (indicating poorer glycemic control) track into the first 6 months postdiagnosis.